2014
DOI: 10.1007/s00125-014-3404-8
|View full text |Cite
|
Sign up to set email alerts
|

A priori-defined diet quality indexes and risk of type 2 diabetes: the Multiethnic Cohort

Abstract: Aim Dietary patterns have been associated with type 2 diabetes incidence, but little is known about the impact of ethnicity on this relation. This study evaluated the association of four a priori dietary quality indexes and type 2 diabetes risk among whites, Japanese Americans, and Native Hawaiians in the Hawaii component of the Multiethnic Cohort (MEC). Methods After excluding participants with prevalent diabetes and missing values, the analysis included 89,185 participants (11,217 cases). Dietary intake wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
94
3
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 102 publications
(106 citation statements)
references
References 44 publications
5
94
3
4
Order By: Relevance
“…40 In the Hawaii component of the MEC, high scores for the DASH were related to a 10–30% lower risk of Type 2 diabetes, whereas the AHEI-2010 and aMED score showed weaker associations, and the HEI-2010 was not related to the risk of Type 2 diabetes. 41 When looking into individual components for the HEI-2010, which had stronger associations compared with the other three indexes in the current study, 4 components, greens and beans, dairy, sodium, and empty calories, among the 12 components showed a statistically significant association with colorectal cancer risk. The associations with the aMED score were less strong than those with the other three indexes.…”
Section: Discussionmentioning
confidence: 52%
“…40 In the Hawaii component of the MEC, high scores for the DASH were related to a 10–30% lower risk of Type 2 diabetes, whereas the AHEI-2010 and aMED score showed weaker associations, and the HEI-2010 was not related to the risk of Type 2 diabetes. 41 When looking into individual components for the HEI-2010, which had stronger associations compared with the other three indexes in the current study, 4 components, greens and beans, dairy, sodium, and empty calories, among the 12 components showed a statistically significant association with colorectal cancer risk. The associations with the aMED score were less strong than those with the other three indexes.…”
Section: Discussionmentioning
confidence: 52%
“…In the Multiethnic Cohort, significant associations with type 2 diabetes were observed for DASH in non-Hispanic white men and women, Japanese American women, and Native American men, whereas AHEI and an alternative MeDS were associated with diabetes in non-Hispanic white participants only; the HEI was not significantly associated with diabetes in any ethnic or sex group (21). The authors suggested that differences in associations may have been due to particular consumption patterns and food components, particularly as most scores were originally developed in non-Hispanic white populations.…”
Section: Discussionmentioning
confidence: 96%
“…However, the composition, weight, and cutoffs of intake of the foods and nutrients included in each score vary widely (4,11), suggesting that their association with disease outcomes may also vary. Studies that have directly contrasted scores have been inconsistent; some show that all scores predict death, risk of diabetes (12)(13)(14) and cardiovascular disease (CVD) (13,(15)(16)(17), or weight changes (18) with comparable magnitude of association, whereas others show larger differences in the association of various scores and cardiometabolic markers within a population (19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Although there was no apparent association between ideal PA and ideal diet with incident diabetes mellitus in our analysis, both have been associated with a reduction in diabetes mellitus risk in previous studies. [32][33][34][35] Data from the Diabetes Prevention Program showed that weight loss achieved through PA and a healthy low-fat, lowcalorie diet reduced the incidence of diabetes mellitus by 61% in blacks, when compared with placebo. 5 Diabetes mellitus risk reduction was greatest in the lifestyle group, compared with the other groups.…”
Section: Discussionmentioning
confidence: 99%